Beta-alanine fails to improve on 5000 m running time despite increasing PAT1 expression in long-distance runners - Franco, G. S.; Noronha, N. Y.; Oliveira, B. A.; Ferreira, F. C.; Pinto, A. P.; Brandao, C. F.; Papoti, M.; Nonino, C. B. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Beta-alanine has become a dietary supplement widely used by athletes due to its ergogenic effect. However, there is still no consensus on the performance benefit of beta-alanine on exercise lasting longer than ten minutes. The present study aimed to evaluate the effect of beta-alanine supplementation on running performance and the expression of TauT and PAT1. METHODS: This double-blind, randomized study enrolled 16 long-distance runners (37±8 years) who were randomly allocated to two groups: placebo (PLA) and beta-alanine (BA) (4.8 g/day 1) for four weeks. Maximal oxygen consumption, anthropometry, body composition, and food intake were determined. Before and after the intervention, the athletes undertook a 5000 m running time trial. Venous blood (TauT and PAT1 expressions) and ear lobe capillary blood (lactate) collected before and after exercise. Between tests, we monitored the training variables. RESULTS: The results were analyzed by t-tests and an ANOVA of repeated measures, with Sidak`s post hoc (P<0.05). PLA exhibited lower body fat than BA (8.7±2.2 vs. 11.5±2.8%, P=0.04). After supplementation, there was an increase in PAT1 expression in BA when compared to PLA (1.17±0.47 vs. 0.77±0.18, P=0.04). No significant differences were shown for the 5000 m running time in PLA (PRE: 1128±72; POST: 1123±72s) and BA (PRE: 1107±95; POST: 1093±86s). CONCLUSIONS: Although beta-alanine supplementation increased PAT1 expression, there was no statistically significant improvement in 5000 m running performance. However, individual responses should be considered as the BA showed a higher delta than the PLA.